Impact of Training Courses on Skill Development and Performance Enhancement of Private Sector Employees in the Eastern Region of Saudi Arabia - Huwaishil, Fatima Ahmed Mohammed (Journal of Economic, Administrative and Legal Sciences, 2025)
This research examines the impact of training courses on developing employee skills and improving their performance in private sector companies in the Eastern Province of Saudi Arabia, highlighting the importance of continuous training in developing human resources and increasing their productivity in light of the rapid changes in the labor market. The research aimed to determine the importance of training courses and measure their impact on employee performance, in addition to identifying the factors affecting their effectiveness and proposing recommendations to enhance the role of training in the Eastern Province. The research used a methodology based on a random sample of employees in private sector companies, with the use of questionnaires as a tool for data collection and analysis using appropriate statistical programs. The results showed that training courses have a positive impact on developing employee skills and improving their performance, with the identification of influential factors such as the type and duration of training and its compatibility with work needs. The research contributes to highlighting the importance of investing in training and development, provides practical recommendations for improving training programs in companies, and supports decision-making related to human resources development.